After the Forfeiture: The MacDonald Kindreds in Ross 1475–1602. - Petre, James (Scottish Historical Review, 2025)
This article considers the MacDonalds who occupied lands in Ross and adjacent territories after the end of their earldom in 1475/6 to their eventual expulsion a century and a quarter later. Accordingly, it covers the years of the MacDonalds of Lochalsh until the extinction of their male line in 1519, moving to the period of the Glengarry MacDonalds. After a brief overview, it proceeds by considering their culture and behaviour and how those characteristics affected—and were affected by—their relations with the crown and other clans. Their relations with their most immediate neighbours, ranging from sometime allies to sometime foes, are then explored in more detail in the second half of the article. The essay reflects that, in some respects, the MacDonalds struggled to compete in the changing circumstances of the time, over which they had little control. Their occasional resort to arms exacerbated their problems. This made them more vulnerable. By degrees, they were eclipsed by the Mackenzies. Their story emerges as an outstanding instance of change in the political and religious geography of the Highlands in the period. The predominance they had enjoyed in the days of their earldom was gone but not forgotten. It is perhaps not too much to claim that they were the beneficiaries of a renowned past—but also its victims.